Botswana Public Expenditure Review - World Bank (Washington, DC, 2013)
The unifying theme of this Public Expenditure Review (PER) is the impending need for Botswana to incorporate into its policy making and planning framework a series of measure to help it transition into an era of diminished diamond revenues. While diamond revenues have enabled rapid development, they have also allowed government to swell, and the public sector is today, with diamonds, a mainstay of the economy. With the decline of diamonds on the horizon, it has become increasingly urgent for Botswana to review and question its management of public finances and the role and objectives of the public sector in the economy, particularly given the large remaining human and social development needs, and the requirements of diversification. While the global economic crisis has helped to bring these issues to the fore, they are long-term challenges that are independent of today's temporary economic difficulties.